1994
DOI: 10.2337/diacare.17.12.1498
|View full text |Cite
|
Sign up to set email alerts
|

Lower Prevalence of Impaired Glucose Tolerance and Diabetes Associated With Daily Seal Oil or Salmon Consumption among Alaska Natives

Abstract: Consumption of seal oil and salmon, high in omega-3 fatty acids, appears to lower the risk of glucose intolerance and is a potentially modifiable risk factor for NIDDM in Alaska Natives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
81
1
2

Year Published

1996
1996
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(89 citation statements)
references
References 9 publications
5
81
1
2
Order By: Relevance
“…Although the controversy in earlier data concerning marine fatty acids and glucose metabolism (Salomaa et al, 1990;Feskens et al, 1991Feskens et al, , 1995Borkman et al, 1993;Adler et al, 1994;Vessby et al, 1994aVessby et al, , b, 2001Pan et al, 1995;Marshall et al, 1997;Baur et al, 1998;Gustafsson et al, 1998;Bjerregaard et al, 2000;Ekblond et al, 2000;Mori et al, 2000;Hu et al, 2001;Salmeró n et al, 2001;Dewailly et al, 2001a, b;van Dam et al, 2002;Wang et al, 2003;Harding et al, 2004;Thorsdottir et al, 2004) may be partly explained by different doses and durations of supplementation in intervention studies, and by different background diets between the study populations, inclusion of subjects with different PPARG Pro12Ala genotypes could also influence the outcome of the study. That PPARG genotype may affect the associations of dietary fat composition with insulin concentrations (Luan et al, 2001) and serum triacylglycerol response to fish oil supplementation (Lindi et al, 2003) was suggested previously.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the controversy in earlier data concerning marine fatty acids and glucose metabolism (Salomaa et al, 1990;Feskens et al, 1991Feskens et al, , 1995Borkman et al, 1993;Adler et al, 1994;Vessby et al, 1994aVessby et al, , b, 2001Pan et al, 1995;Marshall et al, 1997;Baur et al, 1998;Gustafsson et al, 1998;Bjerregaard et al, 2000;Ekblond et al, 2000;Mori et al, 2000;Hu et al, 2001;Salmeró n et al, 2001;Dewailly et al, 2001a, b;van Dam et al, 2002;Wang et al, 2003;Harding et al, 2004;Thorsdottir et al, 2004) may be partly explained by different doses and durations of supplementation in intervention studies, and by different background diets between the study populations, inclusion of subjects with different PPARG Pro12Ala genotypes could also influence the outcome of the study. That PPARG genotype may affect the associations of dietary fat composition with insulin concentrations (Luan et al, 2001) and serum triacylglycerol response to fish oil supplementation (Lindi et al, 2003) was suggested previously.…”
Section: Discussionmentioning
confidence: 99%
“…Especially, long-chain nÀ3 polyunsaturated fatty acids have been found to be associated with enhanced glucose metabolism (Feskens et al, 1991;Adler et al, 1994;Feskens et al, 1995;Baur et al, 1998;Ekblond et al, 2000;Hu et al, 2001;Salmeró n et al, 2001;Thorsdottir et al, 2004) and to lower serum free fatty acid (FFA) concentrations (Gustafsson et al, 1998), although there are also contradictory results (Salomaa et al, 1990;Borkman et al, 1993;Vessby et al, 1994aVessby et al, , b, 2001Pan et al, 1995;Marshall et al, 1997;Bjerregaard et al, 2000;Mori et al, 2000;Dewailly et al, 2001a, b;van Dam et al, 2002;Wang et al, 2003;Harding et al, 2004). It is not known whether some of the discrepancies in previous results could be attributed to differences in the genetic background of the subjects.…”
Section: Introductionmentioning
confidence: 99%
“…With these metabolic effects, the n-3 polyunsaturated fatty acids are centrally placed in the pathogenesis of the insulin resistance syndrome (DeFronzo & Ferrannini, 1991;Reaven, 1993). In a population survey among Alaska Natives, the consumption of seal oil and salmon was associated with a reduced risk of glucose intolerance (Adler et al, 1994), and in a study of Alaska Eskimos (Central and Siberian Yupik and Inupiat) concentrations of some n-3 fatty acids (C18:3n-3 and C20:5n-3) were reduced among those with impaired glucose tolerance or diabetes (Ebbesson et al, 1999). On the contrary, we found that fasting blood glucose increased with the consumption of marine food.…”
Section: Discussionmentioning
confidence: 99%
“…A traditional diet is generally associated with high high-density lipoprotein (HDL) cholesterol, low low-density lipoprotein (LDL), and low triglyceride (Nobmann et al, 1994;Young, 1996;Bjerregaard et al, 1997), but one study from Southern Greenland failed to show this (de Knijff et al, 1992). The consumption of seal oil and salmon was associated with a reduced risk of glucose intolerance among Alaska Natives (Adler et al, 1994), and Alaska Eskimos with impaired glucose tolerance had reduced concentrations of some n-3 fatty acids (Ebbesson et al, 1999). In Igloolik, North West Territories, Canada, a survey in 1969 ± 1970 showed a low mean blood pressure and no rise with age (Hildes and Schaefer, 1973).…”
Section: Introductionmentioning
confidence: 99%
“…Increased dietary intake of ω-3 fatty acids is generally accepted to promote leanness by increasing adaptive hormone release from the endocrine pancreas (46,47). eCBs are derived from arachidonic acid (20:4), an ω-6 PUFA.…”
Section: -Ag Signaling Modulates β Cell Survival In Pancreatic Pseudmentioning
confidence: 99%